SERIAL NERVE CONDUCTION STUDIES IN A GUILLAIN-BARRÉ SYNDROME VARIANT: THE EVOLUTION OF DEMYELINATING CHANGES. Issue 11 (14th October 2015) - Morgan, Catherine; Wakerley, Benjamin; Fuller, Geraint
Abstract : Guillain Barré syndrome (GBS) varies both in terms of clinical phenotype and underlying pathology. Serial assessments allow greater understanding of the pathophysiology. The evolution of neurophysiological changes is particularly helpful in distinguishing between demyelination and reversible axonal conduction failure. Bilateral facial weakness with distal paraesthesias is a rare subtype of GBS. In the largest case series 64% had abnormalities in motor and 27% in sensory conduction on single neurophysiological assessments; this was interpreted as a demyelinating neuropathy. We report an 18-year-old male with bilateral lower motor neurone facial weakness preceded by distal paraesthesias following a 'flu-like illness. Examination of power and sensation was normal. Deep tendon reflexes were present. Cerebrospinal fluid showed albuminocytologic dissociation. By 6 weeks his facial weakness had almost completely resolved without treatment. Serial nerve conduction studies were performed. The first study (day 4) found prolonged distal motor latency and delayed F waves in posterior tibial and common peroneal nerves; normal sensory studies. Second study (day 18) found distal motor latencies and F waves had increased in upper and lower limb nerves. Third study (day 60) found improvement but abnormalities remained with changes similar to the first study. The neurophysiological changes became more marked while he improved clinically. These serial studies confirmed the primary pathological process of this GBS variant to be demyelination.